Pemanfaatan Teknologi Informasi, Profesionalisme, Pengalaman Kerja dan Kinerja Auditor - Putra, I Made Edy Purnama; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 33 No 4 (2023), 2023)
This study aims to examine the effect of the use of information technology, professionalism and work experience on auditor performance. This research was conducted at the Bali Province Public Accounting Firm (KAP). The number of samples is 52 people, with the method of determining the sample in this study using a purposive sampling technique. Data collection through survey methods with questionnaire techniques. The data analysis technique used is multiple linear regression analysis. Based on the results of the analysis, it was found that the use of information technology, professionalism and experience had a positive effect on auditor performance. This proves that auditor performance is influenced by the use of information technology, professionalism and experience which are very important for every auditor to have. Keywords: Utilization Of Information Technology; Professionalism; Experience; Auditor Performance